1991
DOI: 10.1111/j.1574-6968.1991.tb04783.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic relationships among the rickettsiae of the spotted fever and typhus groups

Abstract: Using immunoblots to analyze antigenic relationships among the pathogenic spotted fever and typhus group rickettsiae, I found that the rickettsial lipopolysaccharide (LPS) was a group‐specific antigen. All the rickettsiae examined had 135‐kDa and 58‐kDa protein antigens. The spotted fever rickettsiae and Rickettsia canada had, in addition, 190‐kDa protein antigens which were antigenic analogs of previously described protective antigens of R. conorii and R. rickettsii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1
9

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 18 publications
1
25
1
9
Order By: Relevance
“…Ladder bands of SFG and TG rickettsiae demonstrated on Western immunoblots have been shown to be polysaccharide in nature (1,32). In the present study, we also showed that ladder bands of R. japonica and R. typhi are polysaccharide (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Ladder bands of SFG and TG rickettsiae demonstrated on Western immunoblots have been shown to be polysaccharide in nature (1,32). In the present study, we also showed that ladder bands of R. japonica and R. typhi are polysaccharide (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…It has been reported that the antigenicity of rickettsial LPS is group specific, which has been demonstrated by using monoclonal antibody, antisera against SFG and TG rickettsiae, and convalescent-phase sera from patients with Rocky Mountain spotted fever (3,10,15,32). However, Western immunoblotting in the present study (Fig.…”
Section: Discussioncontrasting
confidence: 46%
“…The SFG rickettsiae consist of more than 20 named species, which are transmitted by tick bite except for R. akari (mite-borne) and R. felis (flea-borne). Antibodies to LPS antigens cross-react among organisms within the same biogroup, but do not crossreact between the two groups (Vishwanath, 1991). There are two major outer membrane proteins in Rickettsia OmpA (Sca 0) and OmpB (Sca5).…”
Section: Etiologic Agentsmentioning
confidence: 99%
“…Rickettsia prowazekii causes epidemic louse-borne typhus fever, one of the most important infectious diseases of the last 500 years from the perspective of its historic impact (Zinsser, 1935;Traub et al, 1978). These obligately intracellular bacteria are closely related genetically and share many antigenic and biologic characteristics (Vishwanath, 1991;Roux and Raoult, 1995;Roux et al, 1997;Stothard and Fuerst, 1995). Their shared antigens include the group-specific lipopolysaccharide and many epitopes of the major immunodominant surface protein.…”
mentioning
confidence: 99%